MITIGATION OF VEGETABLE PRODUCTION RISK WITH HYDROPONIC TECHNIQUES FOR BEGINNER FARMERS USING HOUSE OF RISK AND FUZZY LOGIC METHODS - Neng Rika Lisdayanti Nurrohmah; Ivonne Ayesha; Widhi Netraning Pertiwi (Journal of Social and Economics Research, 2025)
This study aims to identify, analyze, and map production risks in hydroponic vegetable cultivation and formulate appropriate risk mitigation strategies for novice farmers. The method used in this study is HOR (House of Risk) which is used to identify risk sources (risk agents) and prioritize mitigation actions based on severity and occurrence values. In addition, fuzzy logic is used to provide a deeper understanding of the level of relationship between each risk source and the handling strategy. Based on the results of the analysis at the research location (FL), 16 risk events and 27 risk causes were identified in the hydroponic vegetable production process. The risk with the highest ARP (Aggregate Risk Potential) value reached 648, indicating a high potential for loss if not handled properly. Through risk mapping using the Pareto method, it was found that the three main risk causes that need to be prioritized are: 1) inadequate greenhouse conditions (related to temperature, humidity, and air circulation), 2) pest and disease attacks, 3) worker negligence in handling seed containers. Based on the identification of priority risks, 11 risk mitigation strategies were formulated to reduce the risks from recurrence, as indicated by the highest effectiveness/difficulty (ETDk) scores. The results of this study are expected to serve as a practical reference for novice farmers in managing hydroponic production risks more effectively and sustainably.